If a cot θ + b cosec θ = p and b cot θ + a cosec θ = q, then p² – q² =
Boost your Class 10th Maths preparation with NCERT solutions and MCQ-based questions from Chapter 9 Some Applications of Trigonometry. Practice exercise questions short-answer problems and clear explanations to master the real-life applications of trigonometric concepts like heights and distances. These resources are crafted as per the CBSE syllabus for thorough exam readiness. Consistent practice will sharpen your problem-solving skills and help you excel in board exams. Utilize step-by-step solutions and revision notes designed to guide students toward success. Start practicing now!
Share
We are given the equations:
a cotθ + b cosecθ = p — (1)
b cotθ + a cosecθ = q — (2)
We need to find the value of p² – q².
Step 1: Recall the identity for p² – q²
The difference of squares formula states:
p² – q² = (p + q)(p – q).
Thus, we first calculate p + q and p – q.
Step 2: Add equations (1) and (2)
Add the two equations:
(a cotθ + b cosecθ) + (b cotθ + a cosecθ) = p + q.
Simplify:
(a + b)cotθ + (a + b)cosecθ = p + q.
Factor out (a + b):
(a + b)(cotθ + cosecθ) = p + q. — (3)
Step 3: Subtract equation (2) from (1)
Subtract equation (2) from equation (1):
(a cotθ + b cosecθ) – (b cotθ + a cosecθ) = p – q.
Simplify:
(a – b)cotθ + (b – a)cosecθ = p – q.
Factor out (a – b):
(a – b)(cotθ – cosecθ) = p – q. — (4)
Step 4: Substitute into p² – q²
Using the identity p² – q² = (p + q)(p – q), substitute the expressions for p + q and p – q from equations (3) and (4):
p² – q² = [(a + b)(cotθ + cosecθ)] × [(a – b)(cotθ – cosecθ)].
Simplify:
p² – q² = (a + b)(a – b) × (cotθ + cosecθ)(cotθ – cosecθ).
Step 5: Simplify further using the difference of squares
The term (cotθ + cosecθ)(cotθ – cosecθ) is a difference of squares:
(cotθ + cosecθ)(cotθ – cosecθ) = cot²θ – cosec²θ.
From the trigonometric identity:
cosec²θ – cot²θ = 1,
we can write:
cot²θ – cosec²θ = -1.
Substitute this into the expression for p² – q²:
p² – q² = (a + b)(a – b) × (-1).
Simplify:
p² – q² = -(a + b)(a – b).
Expand (a + b)(a – b) using the difference of squares:
(a + b)(a – b) = a² – b².
Thus:
p² – q² = -(a² – b²).
This question is related to Chapter 8, “Introduction to Trigonometry,” from the Class 10th NCERT Mathematics textbook. Answer the question using your knowledge and understanding of the chapter.
For more please visit here:
https://www.tiwariacademy.in/ncert-solutions/class-10/maths/